Analisis Kesalahan Berbahasa Indonesia Tataran Ejaan Menulis Karangan Siswa Kelas VIII SMP Negeri 7 Gunungsitoli - Grace Dominggos Febrini Zendrato; Riana (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to analyze language errors in the expository essays of class VIII students at SMP Negeri 7 Gunungsitoli. This research is a qualitative descriptive study. The data for this research is the worksheet of students who wrote expository essays. The data source in this research was class VIII students at SMP Negeri 7 Gunungsitoli. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it shows that spelling errors in class VIII students at SMP Negeri 7 Gunungsitoli included 104 errors consisting of: 48 errors in the use of capital letters were found, including 27 errors in usage at the beginning of sentences, 18 errors in place names, in There is 1 error in the divine name, and there are 2 errors in the title of the essay. There was only 1 error in using italics. There were 25 errors in writing derived words, including 24 errors in the prefix and 1 error in the suffix. There were 6 errors in writing the word re-form. There were 6 errors in writing prepositions found. There were 18 errors in the use of punctuation marks, including 8 errors in the use of the dot (.), 4 errors in the use of the comma (,) and 6 errors in the use of the hyphen (-).